1995
DOI: 10.1007/bf01215646
|View full text |Cite
|
Sign up to set email alerts
|

Axon-glial relationships in the anterior medullary velum of the adult rat

Abstract: The anterior medullary velum is a thin sheet of CNS tissue which roofs the rostral part of the IVth ventricle and contains fascicles of myelinated fibres which, in part, arise from the nucleus of the IVth cranial nerve. This study used histochemical, immunohistochemical, and intracellular dye-injection techniques to describe cellular interrelationships in the velum in whole-mounts and in sections. Rip antibody-stained whole mounts provided a unique description of both oligodendrocyte units (defined as an oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Neuronal populations may have previously been overlooked because of these studies concentrating mainly on the IVth tract region (Sliney et al, 1981), where in this present study, very few neuronal somata were in fact observed. Also, the smaller size of the neurones described here (all neuronal diameters between 6 and 15 m) compared with the larger unipolar cells both in this study (45 m) and those of Berry et al (1995) may have been another factor. Studies are now under way to assess possible cell-cell interactions and circuitry in the adult rat AMV.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Neuronal populations may have previously been overlooked because of these studies concentrating mainly on the IVth tract region (Sliney et al, 1981), where in this present study, very few neuronal somata were in fact observed. Also, the smaller size of the neurones described here (all neuronal diameters between 6 and 15 m) compared with the larger unipolar cells both in this study (45 m) and those of Berry et al (1995) may have been another factor. Studies are now under way to assess possible cell-cell interactions and circuitry in the adult rat AMV.…”
Section: Discussionmentioning
confidence: 56%
“…Brains were placed in fixative at 4°C for 1 hour and then placed in PBS for 1 hour at room temperature. Brains were then transferred to a Petri dish containing PBS, and under a binocular-scope, the AMV were dissected free from the inferior colliculi and cerebellum (see Berry et al, 1995).…”
Section: Materials and Methods Tissue Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesions were placed in the anterior medullary velum (AM V) (Berry et al, 1995) of Avertin-anesthetized, adult Wistar rats using a retractable, curved needle, guarded by a trochar, devised specifically for this purpose. With the needle withdrawn into the trochar, the instrument was introduced through the posterior atlanto-occipital membrane into the IVth ventricle until the tip of the instrument lay in the most rostral portion of the ventricle.…”
Section: Anterior Medullary Velum Lesionmentioning
confidence: 99%